A Breed Apart?: A comparative study of investigative journalists and US journalists. (4th March 2017) - Lanosga, Gerry; Willnat, Lars; Weaver, David H.; Houston, Brant
Abstract : This study reports selected comparative findings from two national surveys of 861 self-identified investigative journalists and 1080 US journalists drawn from the profession as a whole. The study examines possible predictors of journalistic roles and support for controversial reporting techniques, including demographics, organizational context, and journalistic attitudes. It finds notable distinctions in demographic factors, perceptions of journalistic roles, and attitudes toward controversial reporting practices. As expected, investigative journalists are more likely to express support for the adversarial function of journalism. Among US journalists, those who support the adversarial approach are characterized by significant attitudinal differences. The study suggests the need for more research that analyzes distinct practitioner groups identified by the kind of journalism they produce.